Observations of Correlated Behavior of Two Light Torsion Balances and a Paraconical Pendulum in Separate Locations during the Solar Eclipse of January 26th, 2009 - A. F. Pugach; D. Olenici (Advances in Astronomy)
On January 26th, 2009, simultaneous observations of the reactions of two very light torsion balances (Kiev, Ukraine) and a paraconical pendulum (Suceava, Romania, 440 km away) were performed during a solar eclipse that was not visible at those locations but only in the Indian Ocean. Significant correlation between the behavior of the torsion balances and the pendulum was observed. The conclusion is that a solar eclipse influences the reactions of torsion balances and pendulums, even in areas of the Earth where it is not optically visible.